Analysis of Fitness Status Variations of Under-16 Soccer Players Over a Season and Their Relationships With Maturational Status and Training Load - Nobari, Hadi; Silva, Ana Filipa; Clemente, Filipe Manuel; Siahkouhian, Marefat; García-Gordillo, Miguel Ángel; Adsuar, José Carmelo; Pérez-Gómez, Jorge (Frontiers in Physiology, 2021)
The purposes of this study were (i) to analyze the variations in maximal oxygen consumption (VO2max), maximal heart rate (HRmax), heart rate at rest, acceleration, maximal speed, agility, anaerobic sprint test (RAST) of peak power (RPP), RAST of minimum power, RAST of average power (RAP), and RAST of fatigue index (RFI) during the competitive season, using maturation status and accumulated training load as covariates, and (ii) to describe the differences between responders and non-responders in relation to baseline levels. Twenty-three elite players from the same team competing in the national under-16 competitions were evaluated for 20 weeks in period 1 (before league), middle (mid league), and period 2 (after league). The VO2max (p = 0.009), maximal speed (p = 0.001), RPP (p < 0.001), RAP (p < 0.001), and RFI (p < 0.001) significantly changed across the assessment periods. Interestingly, using accumulated training load and maturation status as covariates revealed no statistical significance (p > 0.05). When analyzing responders and non-responders, only HRmax (between periods 1 and 2) showed no differences between the groups. As a conclusion, it can be seen that accumulated training load and maturation status play an important role in the differences observed across the season. Thus, coaches should consider the importance of these two factors to carefully interpret fitness changes in their players and possibly adjust training decisions according to the maturation level of the players.